The Influence of Intellectual Capital, and Capital Structure on Financial Performance - Ahmad Ikbal; Abdullah (Yayasan Ilomata, 2023)
The primary aim of this study is to investigate how capital structure and intellectual capital affect the financial performance of banking institutions that are publicly traded on the Indonesia Stock Exchange over the period from 2018 to 2022. The research employed a purposive sampling approach to select its sample, resulting in the collection of 180 data observations from 36 companies over a five-year span. The analysis in this study was conducted using multiple linear regression techniques, utilizing IBM SPSS software for the analysis. The research findings indicate that capital structure does not exert a substantial impact on financial performance. In contrast, intellectual capital exhibits a notably positive influence on financial performance.